Secure Data Storage Scheme Using Blockchain in Federated Cloud - Munwar, Shaik; Ramani, K; Madhavi, K (International Journal of Computer Sciences and Engineering, 2025)
With the development of Internet technology, the volume of data is growing immensely. To deal with large-scale data, cloud storage has gained great attention from organizations and businesses because of its easy and efficient to adoption. Traditional cloud storage has come to rely almost exclusively on large storage providers acting as trusted third parties to transfer and store data. Though, cloud Provider offers considerable security features, with increasing demands and usage, these centralized systems have become major targets for hacks and data breaches. This makes the data vulnerable and prone to tampering. In this paper, to address the above problems we proposed a blockchain-based security scheme for distributed cloud storage, where users can divide their own files into encrypted data chunks, and upload those data chunks randomly into the federated clouds.